GÜMÜŞKÖY (KÜTAHYA) MADEN SAHASINDA KARASAL BITKILERDE ZN VE SB BIOAKÜMÜLASYONLARI - SALEH, ZHELA ZAKARIYA SALEH (Fırat Üniveristesi, 2017)
Gümüşköy (Kutahya) Ag, As ve Pb yatağı Kutahya'nın yaklasık 25 km batısında yer almaktadır.

Gumuskoy Ag, As and Pb deposıts ıs located to about 25 km west of Kutahya in this region, the units cropping out in the study area are composed of metamorphic, volcanic and sedimentary rocks and their ages range from Upper Palesozoic to Quaternary.
The Zn and Sb bioaccumulations in the terrestrial plants at the Gumuskoy (Kütahya) mining area
Keywords: Jeoloji Mühendisliği